2004
DOI: 10.1148/radiol.2331030028
|View full text |Cite
|
Sign up to set email alerts
|

Acute Stroke Assessment with CT: Do We Need Multimodal Evaluation?

Abstract: The presented multimodal CT evaluation improves detection rate and prediction of the final size of infarction in comparison with unenhanced CT, CT angiography, and perfusion CT alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(69 citation statements)
references
References 34 publications
5
61
0
3
Order By: Relevance
“…The high quality of CBF and CBV maps found in our study has been reported in numerous publications; 2,3,28,30 our findings additionally show that CBF and CBV maps of DC and MS are very comparable in terms of quality and diagnostic value. In cases with poor source dataset quality, CBF DC and CBV DC maps were slightly superior to CBF MS and CBV MS maps.…”
Section: Qualitative Analysissupporting
confidence: 87%
“…The high quality of CBF and CBV maps found in our study has been reported in numerous publications; 2,3,28,30 our findings additionally show that CBF and CBV maps of DC and MS are very comparable in terms of quality and diagnostic value. In cases with poor source dataset quality, CBF DC and CBV DC maps were slightly superior to CBF MS and CBV MS maps.…”
Section: Qualitative Analysissupporting
confidence: 87%
“…Multimodal stroke CT, combining NECT, CTA, and PCT, demonstrated its feasibility to assess patients with acute stroke. 23 The next step toward a more individualized therapy of stroke was to use an intra-arterial application of rtPA, which was recommended as an alternative therapy beyond the 3-hour time window. 24 Most publications use the recanalization success and the clinical outcome as a treatment control and do not correlate their data to tissue outcome.…”
Section: Discussionmentioning
confidence: 99%
“…2 Multimodal CT increases the sensitivity of stroke detection as well as the prediction of the final size of the infarct, compared with unenhanced CT, CTA, and PCT alone. 12 Moreover, these CT methods can be used immediately after unenhanced CT, they can be used to exclude hemorrhage, imaging time is fast (Ͻ 5 minutes), and no special hardware is required. 13 Second, fewer trips to the CT scanner during a patient's hospital stay reduce both transfer-related complications and clinicians' and CT technologists' workloads, increasing efficiency.…”
Section: Discussionmentioning
confidence: 99%